The Role Of Professional Ethics In The Formation Of An Aesthetic Worldview Of Young People. - Khamraev Samariddin Bakhrilloyevich (Zien Journals, 2025)
This article covers the role and tasks of professional ethics and education in the formation of aesthetic worldview and education of young people. Respect for the profession, honesty, beauty and responsibility are decided on the basis of aesthetic norms in youth thinking. At this point, a scientific analysis of the concept of educational education, its necessary conditions, its significance today, based on the social characteristics of its development
Keywords: Youth; personality; moral and aesthetic education